Загальні механізми формування системи цитування наукових статей - Гогунський, Віктор Дмитрович; Яковенко, Володимир Олександрович; Лященко, Тамара Олексіївна; Отрадська, Тетяна Василівна (НТУ "ХПІ", 2016)
Аналіз життєвого циклу наукових публікацій свідчить, що цитування статей має властивості марківських процесів. Комунікації змінюють ймовірності станів системи з рухом від стану відсутності інформації про публікацію до ознайомлення з нею через стан позитивного відношення до її цитування. Доведено, що використання авторами систем Google Scholar, ORCID, Mendeley, Academia, ResearchGate для розміщення публікацій збільшується частка статей, які є доступними колегам у Інтернет-просторі.

Transformation competitive environment of higher education in the creation of effective mechanisms of management research encourages research teams and individual researchers to analyze their activity Publication search methods for improvement of citations of scientific publications. The paper analyzed the life cycle of scientific publications and show that the way to promote scientific articles in the world community inherent properties of Markov processes. Application of Markov chains allows obhrunuvaty need for active participation of the authors in the distribution of its publications in different scientometric databases, repositories of scientific and social networks.. Markov model to describe decomposition of scientists made certain discrete states and proposed a schematic diagram of transitions between them. The model's 5A fully reflect the properties of the system. Communication influences the probability of changing system states with consistent movement along the trajectory from a lack of information about the publication to familiarize with it because of the positive attitude to state its citation. This is a must as well as a negative attitude to the publications. Proved that improve performance citation of scientific publications in the case of using Google Scholar, ORCID, Mendeley, Academia, ResearchGate and others. The active participation of authors in their publications available in these systems leads to an increase in the proportion of articles that are available to colleagues in the global scientific community that is becoming one of the factors of increase in citations.
General mechanisms of citation system of scientific articles
Keywords: публікація; активність; автор; ланцюг Маркова; наукометрика; publications; activity; author; Markov chain